Peran Modal Sosial dalam Melestarikan Subak Bukti Batan Badung di Desa Gulingan Kecamatan Mengwi Kabupaten Badung - KUSUMA, I GUSTI PUTU SASTRA PUTRA; WINDIA, I WAYAN; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
Role of Social Capital in Preserving Subak Bukti Batan Badung in Gulingan Village, Mengwi Sub-district, Badung Regency Subak Bukti Batan Badung is one of the subaks found in Bali. The area of Subak Bukti Batan Badung was previously 65,25 hectares and had undergone land conversion of 7,25 hectares. Seeing the current development, it is highly likely that the existence of Subak Bukti Batan Badung could be threatened. Thus, there is a need for the role of social capital is preserving Subak Bukti Batan Badung. The data analysis method used was descriptivr qualitative.The results of this study showed that social capital owned by Subak Bukti Batan Badung to keep its sustainability was good which could be seen in: (1) the farmer’s belief in other farmers, the farmer’s belief in subak administrators, farmer’s belief in the government program and religious rituals, and the farmer’e belief in the cooperatives, (2) the norms; awig-awig owned was not strong enough to suppress land conversion. Other norms were still strong and obeyed by all the subak member. (3) The social network owned could br said to be good, it could be seen from subak’s relationship with banjar/adat village, subak relationship with Public Work and Agricultural Departements.The suggestion that can be made from this research is to reinforce regulation accompanied bu sanction for related parties violating the awig-awig and awareness of subak members not to do land conversion.